PENGARUH LIKUIDITAS, LEVERAGE, PROFITABILITAS, DAN JAMINAN TERHADAP PERINGKAT OBLIGASI PADA PERUSAHAAN NON KEUANGAN YANG DIPERINGKAT OLEH PT PEFINDO YANG TERDAFTAR DI BURSA EFEK INDONESIA - Wulan Suryandani; Yana Mardiana (Program Sarjana Manajemen Universitas Internasional Batam, 2021)
This study was conducted with the aim of testing and explaining the effect of liquidity, leverage, profitability and guarantees on bond ratings of non-financial companies rated by PT Pefindo. The type of data used is secondary data from each non-financial sector company obtained from the official website of the Indonesia Stock Exchange through ww.idx.co.id and PT Pefindo's website www.pefindo.com. The sampling technique was carried out by purposive sampling. The number of samples used in this study are 10 non-financial companies that issue bonds and their bonds are rated by PT Pefindo for the 2017-2019 period. The data analysis technique used was logistic regression analysis using the IBM SPSS Statistics 22 program. The results showed that liquidity, leverage, profitability, and guarantees had no significant positive effect on bond ratings. The result of the coefficient of determination shows a value of 0.122 which means that the variables of liquidity, leverage, profitability and guarantee are able to explain the bond rating variable of 12.2% while the remaining 87.8% is explained by other factors outside the research model.